Simplify

- 3/4r + 3 - 5/6r - 6

1 answer

To simplify this expression, combine like terms.

First, combine the terms with "r":

(-3/4r) - (5/6r)

To add these fractions, you need a common denominator of 12:

(-3/4r) - (5/6r) = (-9/12r) - (10/12r)

Next, combine the constant terms:

3 - 6 = -3

Putting it all together:

(-9/12r) - (10/12r) + (-3)

Combine the "r" terms first:

-19/12r + (-3)

This can be written as:

-19/12r - 3

So the simplified expression is -19/12r - 3.
Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions